Directive Speech Acts in Raditya Dika's Podcast "If You Need Help, Watch This!" - Naibaho, Winda Pramesti; Simanjuntak, Dairi Sapta Rindu; Simanjuntak, Maretha Damai; Girsang, Natal Eliazer (Jurnal Bahasa Indonesia Prima (BIP), 2026)
This study aims to describe the form and function of directive speech in Raditya Dika's podcast entitled "THOSE WHO NEED HELP, WATCH THIS!". The method used is a descriptive qualitative approach. Data in the form of oral speech containing directives were obtained through listening and recording techniques, then transcribed, identified, and classified into six forms, namely requests, questions, orders, prohibitions, granting permissions, and advice. The results of the study showed that there were 34 directive speeches consisting of 3 requests, 15 questions, 3 commands, 9 prohibitions, 1 granting of permission, and 1 advice. The most dominant form is the question. Pragmatically, the dominance of the directive of questions shows that the educational strategies in this podcast are more realized through information extraction and dialogical clarification. In addition, the existence of prohibitory speech and advice related to fire safety procedures shows that there are aspects of preventive education and increased public safety awareness. Thus, this podcast has the potential to be used as a medium for learning Indonesian, especially in the study of directive speech, language politeness, and persuasive communication in digital discourse.